Development of Experimental Materials on Moral Judgment in Sport: Evidence From Chinese Athletes - Chen, Zuosong; Wang, Dong (Frontiers in Psychology, 2019)
Objectives: The existing scales for moral judgment in sport have some limitations if they were used for cognitive neural research on moral judgment in sport. Developing a set of experimental materials with good validity is thus warranted. The purpose of this study was to develop experimental materials, which can be used in cognitive neuroscience research on moral judgment in sport. Design: Study 1 was a qualitative study and Study 2 was a within-subject design. Method: In Study 1, a qualitative method was adopted to assess types of moral misconduct among Chinese athletes, based on news reports of Chinese athletes’ moral misconduct collected from the Internet and from interviews with Chinese elite athletes. In Study 2, typical examples were selected from a qualitative analysis based on the types of moral misconduct observed among athletes in Study 1. The examples were then compiled, controlled, and modified. The validity of the developed experimental materials was evaluated. Results: The moral misconduct observed in Chinese athletes can be divided into the following four categories: violent behavior, doping, match-fixing or tanking, and self-reported dishonesty. Subject analysis and item analysis consistently found that the experimental materials developed for moral judgment based on the four categories were significantly different in six aspects, including the rate of participants’ agreement to the proposed resolution (FSubject (3, 184)=236.60, p=0.00; FItem (3, 156)=471.17, p=0.00), decision time (FSubject (3, 184)=23.69, p=0.00; FItem (3, 156)=3.13, p=0.03), moral conflict (FSubject (3, 184)=3.70, p=0.01; FItem (3, 156)=10.71, p=0.00), moral acceptability of the behavior (FSubject (3, 184)=58.22, p=0.00; FItem (3, 156)=110.69, p=0.00), emotional valence (FSubject (3, 184)=3.41, p=0.02; FItem (3, 156)=3.11, p=0.03), and emotional arousal (FSubject (3, 184)=1.32, p=0.27; FItem (3, 156)=5.09, p=0.00). The experimental materials developed were not affected by the type of sport. Conclusions: The developed experimental materials can be used as experimental materials for cognitive neuroscience research on moral judgment in sport.